THE EFFECTIVENESS OF PREGNANCY EXERCISE AND EFFLEURAGE MASSAGE ON BACK PAIN INTENSITY IN TRIMESTER III PREGNANT MOTHERS - lestari, ranti ranti; septica, qorry qorry; yanti, damai damai (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2024)
Physiological changes in pregnany occurs to an increase in the hormon estrogen, progesteron and adrenalin so that it can cause changes in the body of pregnant fell discomfort musculoskeletal system which causes back pain. Back pain in pregnancy is back pain that occurs in the lumbosacral area, this complaint can be lost by doing physical ativities by carring out physical activites of pregnancy and massage effleurage. To find out the effevtiveness of pregnancy exercise and massage effleurage treatment on decreasing back pain in pregnan women at Public Health Center Muka Cianjur District April-June 2022 period. This study used Quasi Experiment Design with pre test and  post test nonequivalent. Respondent were 30 people divided in 2 group in prenatal pregnancy exercise and massage effleurage as an alternative therapy. The sampling tehnique using purposive sampling technique. The data of back pain with pain scale measurement using Visual Analoge Scale (VAS). Data were analyzed using statistical test of Wilcoxon and Mann Whitney. Result  The average low back pain in prenatal preganacy exercise group was 1,45±0,06 wich is lower than massage effleurage 2,78±0,47 on the level of low back pain pregnancy women with 0,31 p-value 0,000> 0,05.  Pregnancy exercise effectively help reduce back pain in pregnant.